Influence of incubation period on membrane patch color for insoluble contaminant measurement in degraded hydraulic oils - Pravda, Stepan; Sedenka, David; Blata, Jan; Hrabovsky, Leopold (Frontiers in Mechanical Engineering, 2024)
Insoluble contaminants or varnish are the result of oil degradation byproducts and sometimes depleted additive molecules. This process is in most cases initiated by thermal stress placed on the oil. In tribology, varnish becomes a significant problem for the lubrication systems of modern complex machinery, as it has severe debilitating effects, such as a loss of operating clearances and heat transfer. Problems arising from varnish buildup in lubricants can be mitigated through timely oil analysis, which provides important information about the oil degradation level and the current potential for insoluble contaminants in the oil. Several laboratory testing methods are available to assess varnish potential. The most widely applied one is colorimetric analysis, also known as Membrane Patch Colorimetry (MPC), due to its relatively quick and cost-effective nature. This study applies the principles commonly used for MPC tests on turbine oils to measure the insoluble contaminants generated by degraded hydraulic fluids. As per ASTM D7843-21 standard, the precision of this testing method for turbine oils is contingent upon the incubation period of the tested sample. We aim to explore modifications to the standard 72-hour incubation period, investigating whether shortening or extending this duration is viable for conducting MPC tests on used hydraulic fluids.